mSphere of Influence: The ever-expanding universe of parasite cell biology - Benjamin Liffner (mSphere)
ABSTRACT Ben Liffner studies the cell biology of apicomplexan parasites. In this mSphere of Influence article, he reflects on two key papers: “Three-dimensional ultrastructure of Plasmodium falciparum throughout cytokinesis” by R. M. Rudlaff, S. Kraemer, J. Marshman, J. D. Dvorin, et al. (PLoS Pathog 16:e1008587, 2020, https://doi.org/10.1371/journal.ppat.1008587) and “Expansion microscopy provides new insights into the cytoskeleton of malaria parasites including the conservation of a conoid” by E. Bertiaux, A. C. Balestra, L. Bournonville, V. Louvel, et al. (PLoS Biol 19:e3001020, 2021, https://doi.org/10.1371/journal.pbio.3001020). These two studies provided Ben with the conceptual framework to understand how parasites are organized in three dimensions, and the technique of ultrastructure expansion microscopy that he has since used to investigate this intriguing area of biology.